2023
DOI: 10.1021/acs.macromol.3c01143
|View full text |Cite
|
Sign up to set email alerts
|

l-Histidine Salt-Bridged Monomer Preassembly and Polymerization-Induced Electrostatic Self-Assembly

Yuanyuan Liu,
Xiyu Wang,
Caihui Luo
et al.

Abstract: Salt bridges are predominant in protein construction and stabilization, yet largely unexplored for polymer nanoparticle synthesis. We herein report the use of l-histidine salt bridges to drive monomer preassembly and two-dimensional electrostatic self-assembly in aqueous photo-RAFT polymerization. l-histidine salt bridges drive the monomer clustering nucleation, complex coacervation, and Coulombic stabilization, leading to the 2 nm ultrasmall clusters and coacervate droplets. Homopolymerization leads to a prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…It is seemingly axiomatic that net charge must be minimized for the precision shape/size control in PIESA. Nevertheless, highly charged salt-tolerant subdomains are omnipresent in cellular proteins organized via site-specific molecular recognition under thermodynamic and kinetic control . We found that aspartic acid ionic H-bonds and histidine salt bridges could stabilize salt-tolerant nanoparticles mainly via enthalpy control. Nevertheless, the electrostatic interactions of oppositely charged polyions lead to entropy gains from release of counterions associated with polymer chains that drive complexation.…”
Section: Introductionmentioning
confidence: 89%
“…It is seemingly axiomatic that net charge must be minimized for the precision shape/size control in PIESA. Nevertheless, highly charged salt-tolerant subdomains are omnipresent in cellular proteins organized via site-specific molecular recognition under thermodynamic and kinetic control . We found that aspartic acid ionic H-bonds and histidine salt bridges could stabilize salt-tolerant nanoparticles mainly via enthalpy control. Nevertheless, the electrostatic interactions of oppositely charged polyions lead to entropy gains from release of counterions associated with polymer chains that drive complexation.…”
Section: Introductionmentioning
confidence: 89%
“…[46][47][48] The monomer/solvent toolkit of PISA has also been greatly enlarged. [49][50][51][52][53][54][55][56] Furthermore, the precise fabrication of polymer assemblies with a high concentration has greatly advanced their applications. In addition to drug and gene delivery, [57][58][59] polymer assemblies prepared via PISA have recently been used as Pickering emulsifiers, 60,61 nano-reactors, 62,63 functional gels, 64,65 coatings, 66,67 nano-splitters, 68 ice recrystallization inhibitors, 69,70 etc.…”
Section: Introductionmentioning
confidence: 99%